HUBUNGAN HARGA DAN KUALITAS PRODUK DENGAN KEPUASAN PELANGGAN PADA TOKO PERLENGKAPAN BAJU SEKOLAH ELIS KOTA BENGKULU - Siti Hanila; Rahmad Hidayat (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The aim of this study is to know the relationship of price and product quality with customer satisfaction at Elis school uniform shop of Bengkulu city. The sample in this study were 50 consumers who purchased school uniform at Elis school uniform shop of Bengkulu city, because all the population in this study were sampled, so the sampling was done by using accidental sampling technique. Data collection methods used is questionnaires and analytical methods used are rank spearman correlation analysis and testing the data with t test.Based on the results of study the price has a relationship with the customer satisfaction at Elis school uniform shop of Bengkulu citywith a correlation value of 0.537, thus the price offered by the shop is relatively or not too expensive or not too cheap. This result is reinforced by hypothesis test result that tcount is greater than t table (4.408> 1.677). This means that the price has a significant relationship with customer satisfaction at Elis school uniform shop of Bengkulu city.Rank spearman correlation for the relationship of product quality with customer satisfaction at Elis school uniform shop of Bengkulu cityhas a strong correlation with correlation value of 0.604, it means that the better quality of the trade by Elis school uniform shop, the higher level of customerssatisfaction. This is reinforced by the hypothesis test result that t count is greater than t table (5.246> 1.677). This means that the product quality has a significant relationship with customer satisfaction at Elis school uniform shop of Bengkulu city.